CYCLOSPORIN A IN THERAPY FOR JUVENILE ARTHRITIS - E S Fedorov; Svetlana Olegovna Salugina (Современная ревматология, 2010)
The paper describes approaches to using cyclosporin A (CsA) in juvenile arthritis (JA). It shows the benefits of combination basic therapy with CsA and methotrexate included into a treatment regimen mainly for systemic JA and JA involving the eye (uveitis) versus monotherapy with the above drugs. Attention is drawn to that the oral dose of glucocorticoids may be decreased when CsA is incorporated into the treatment regimen. CsA is shown to be of value as the drug of choice for the therapy of such a menacing complication of systemic JA as the macrophage activation syndrome